Nilai-Nilai Moral dalam Novel Iyan Bukan Anak Tengah Karya Armaraher: Kajian Sosiologi Sastra - Purba, Yutri Fahira; Lubis, Haris Sutan; Marsella, Emma (Bahasa Indonesia Prima, 2024)
This research uses literary sociology studies to describe the moral values in the novel Iyan Bukan Anak Tengah by Armaraher. This research uses the theory of moral values presented by Wicaksono with a qualitative descriptive method. The data is presented through quotations, narratives, and dialogue between characters that contain moral values. The data collection method is done using reading and recording techniques. The results of the study can conclude that the moral values contained in the novel Iyan Bukan Anak Tengah by Armaraher, first, human relationships with God include gratitude and belief in the existence of God. Second, man's relationship with himself includes patience, courtesy, honesty, self-esteem, longing, fear, resentment, loneliness, sadness, pessimism, and responsibility. Third, human relationships with other humans include caring for others, living in harmony, forgiving, helping, deliberating, respecting others, true love, and keeping promises. Fourth, human relationships with the universe include utilizing natural resources and protecting nature.